Lanolin as a contact sensitizer among cosmetology students and cosmeticians: A pilot study - Maya Lyapina; Aleksandar Shkondrov; Maia Vizeva; Adolf Alakidi; Maria Nikolova; Ilina Krasteva; Valentina Petkova (Pharmacia)
Lanolin is a lipoid—an animal wax obtained from the sebaceous secretions of domestic sheep. According to the European Pharmacopoeia, lanolin is referred to as Adeps lanae. Various lanolin derivatives are used in personal care products, cosmetics, and topical medications, including lanolin oil, wax, alcohol, acetylated, and hydrogenated lanolin. Cosmeticians and cosmetology students may be exposed to lanolin through occupational and educational activities. Lanolin is considered a potential contact sensitizer. This study aims to evaluate the prevalence of contact sensitization to lanolin among cosmeticians and cosmetology students. Skin patch testing with lanolin alcohol was conducted on 109 participants: 37 cosmetology students, 26 cosmeticians, and 46 controls. A high positivity rate (30.8%) was observed, particularly among occupationally exposed cosmeticians who regularly use skin care products. This rate was significantly higher than that of students (p = 0.028), but not significantly different from that of the control group. Proper risk information and comprehensive programs for occupational skin disease prevention are recommended.